Sustainable metal-free carbogels as oxygen reduction electrocatalysts. Issue 31 (22nd May 2017) - Preuss, K.; Tănase, L. C.; Teodorescu, C. M.; Abrahams, I.; Titirici, M.-M.
Abstract : A simple synthesis approach is presented to produce sustainable electrocatalysts with tuneable surface area, porosity, morphology and functionality. Abstract : Tuneable nitrogen doped carbogels have been synthesised by a simple one-pot hydrothermal carbonisation, followed by pyrolysis at 1000 °C, using highly available and low cost precursors such as glucose and ovalbumin. Different physical activation ratios of nitrogen/oxygen were used to demonstrate a sustainable and easy method for changing surface area, pore size and elemental composition in order to investigate their effect on the oxygen reduction reaction when used as electrocatalysts. A ratio of nitrogen mixed with 2% of oxygen was found to be most beneficial for enhancing the catalytic activity by creating a high surface area of 874 m 2 g −1 as well as a favourable ratio of pyridinic to graphitic nitrogen. The influence of sulphur doping and/or boron on the carbogel structure was investigated. Incorporation of sulphur does not interfere with the structure formation, but decreases the surface area and nitrogen content resulting in diminished ORR performance. However, boron doping with boric acid results in a different carbogel structure by acting as a catalyst, creating an altered morphology, surface area, pore properties and higher nitrogen content by fully utilising ovalbumin as a nitrogen source instead of as a structure directing/surface stabilising agent. Nitrogen content is found to determine the limiting current, while the oxygen content has a small influence on the onset potential. An assumed synergistic effect between nitrogen and boron generates higher electron transfer numbers and lower hydrogen peroxide yields in boron nitrogen co-doped carbogels than those observed in purely nitrogen doped systems.